Prescription Opioid Misuse, Abuse, Morbidity, and Mortality: Balancing Effective Pain Management and Safety. Issue 1 (11th September 2015) - Cheatle, Martin D.
Abstract Objective The burgeoning rate of prescription opioid misuse, abuse, addiction, and opioid related overdose deaths has gained substantial professional and national media attention. This manuscript provides a narrative review and critique of the literature on prescription opioid misuse, abuse, addiction and opioid‐related mortality and discusses future research needs in this area. Design Current literature on misuse, abuse, addiction and opioid related fatalities was reviewed in patients with chronic noncancer pain receiving long‐term prescription opioid therapy. Results There have been inconclusive results on the efficacy of long‐term opioid therapy in patients with chronic pain but moderate level evidence of dose‐dependent risk of harm. The estimated prevalence of prescription opioid abuse and opioid use disorders ranges from <1% to 40% due to the paucity of uniform definitions of what constitutes misuse, abuse, and addiction but several recent studies have developed unique methodology to more accurately assess these states in the pain population. The rate of opioid‐related overdose deaths is not inconsequential and a number of patient related and medication specific risk factors have been identified that may provide a basis for risk mitigation strategies. Conclusions Accurately assessing the prevalence of misuse, abuse, and addiction in the pain population has been challenging due to inconsistent definitions between studies. Additional high‐quality research is needed in this area utilizing consistent definitions and in reducing the risk of opioid‐related overdose fatalities.